DESIGN OF AN UNMANNED AUTONOMOUS DRONE TAXI FOR DELIVERY SERVICES IN URBAN ENVIRONMENTS - F.K . Sulaymanova,; F.K. Sulaymanova, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: The rapid growth of urbanization and e-commerce has significantly increased the demand for fast, efficient, and reliable delivery systems. Traditional ground transportation methods often face challenges such as traffic congestion, long delivery times, fuel consumption, and environmental pollution. In this context, unmanned aerial vehicles (UAVs), commonly known as drones, have emerged as an innovative solution for urban logistics. This research focuses on the design and development of an autonomous drone taxi system intended for delivery services in urban environments.The study aims to create an optimized drone design capable of operating safely, efficiently, and autonomously within complex city infrastructures. The research analyzes aerodynamic performance, structural design, payload capacity, navigation systems, battery efficiency, and safety mechanisms. Special attention is given to urban conditions such as high-rise buildings, signal interference, weather conditions, and population density. The proposed drone taxi model integrates modern technologies including artificial intelligence, GPS navigation, obstacle detection systems, and real-time route optimization.